Organophotochemical SNAr Reactions of Mildly Electron‐Poor Fluoroarenes. Issue 18 (30th April 2020) - Sheridan, Thomas; Yayla, Hatice G.; Lian, Yajing; Genovino, Julien; Monck, Nat; Burton, Jonathan W.
Abstract : C–F functionalization of arenes with a range of alcohol and pyrazole nucleophiles has been achieved without the need for metal catalysts or highly electron‐poor substrates. Treatment of fluoroarenes with alcohols or pyrazoles and DDQ under irradiation by blue LED light provides the corresponding substituted products. The procedure is complementary to classical SN Ar chemistry which generally requires basic reaction conditions and high temperatures, and provides products under non‐basic conditions at ≈ 40 °C. Abstract : C–F functionalization of arenes with a range of alcohol and pyrazole nucleophiles has been achieved without the need for metal catalysts or highly electron‐poor substrates. Treatment of fluoroarenes with alcohols or pyrazoles and DDQ under irradiation by blue LED light provides the corresponding substituted products.